Colour and Fastness Properties of Silk Fabrics Dyed With Colours Obtained From The Flowers of The Papaver Rhoeas L. (Common Poppy) - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2012)
In presented study, flowers of the Papaver rhoeas L. plant were used. Usability of the flowers of the Papaver rhoeas L. which has a wide expansion area throughout the world as natural dyes in dyeing the silk fibres was examined. After the silk material was treated with a mordanting process with the common mordanting agents, it was dyed with the dye extracted from the plant through the conventional and ultrasonic methods. L*a*b* values of the dyed material were measured and analyzed by using the CIE L*a*b* colour space system of the samples. Moreover, washing and light fastness properties of dyed materials were examined. It was observed that colour yield increased in dyeing made with natural dyestuff extracted from the Papaver rhoeas L. plant and through the dyeing method performed with environment-friendly ultrasonic energy.
Keywords: Papaver rhoeas L.; Vegetable dye; Silk; Ultrasonic method; Conventional method; COTTON; WOOL